Violência autoprovocada: perfil de pacientes atendidos em Centros de Atenção Psicossocial Infantil (CAPSi) - Oliveira, Angélica Aparecida de (2023)
Self-inflicted violence among children and adolescents is an important health issue. The objective of this study was to characterize and to describe patients with self-inflicted violence from Psychosocial Care Centers for children and adolescents (CAPSi) in São José do Rio Preto, SP, Brazil. Method: This is a descriptive, retrospective, documentary study with a quantitative approach. Data were obtained through the analysis of patients records between January 2019 and December 2021, specifically the cases identified by the CAPSi(s) teams as patients with self-inflicted violence. Data collection was carried out using an instrument built by the researcher and the SPSS Statistics software version 29 was used for the exploratory data analysis. Results: records of 225 patients were identified; most were female (n = 182), enrolled on fundamental school (6th to 9th years) (n =116). Patients’ referrals to CAPSi came mainly from Psychiatric Emergency (n = 69), due to spontaneous demand (n = 48), and from Health Care Unities (n = 38). Previously suffered violence was reported in 117 cases: sexual (n = 71), physical (n = 40), psychological (n = 47) and neglect/abandonment (n = 13). The use of legal and illegal drugs was observed in 47, the most frequent of which were alcohol (n = 32), marijuana (n = 21) and multiple drugs (n = 5). The diagnoses most frequently attributed to patients were mood disorders (n = 178), personality disorders (n = 66) and anxiety disorders (n = 57). Until the end of data collection, 110 were still receiving care through CAPSi; 115 had ended their care due to discharge from the team (n = 34), abandonment or requested discharge (n = 55), transfer to another service (n = 10), change of city (n = 10). The average treatment time at the CAPSi was 17.4 months (±9.7 months). There was no correlation between alcohol xix and drug use and self-inflicted violence, pointing to other predisposing factors. Conclusion: There was a predominance of single-parent families, with a family history of mental disorders and adolescent patients who were victims of previous violence, with self-mutilation (cuts) in the upper and lower limbs. The absence of mandatory notification for self-inflicted violence was identified by some services.